Potret Islam Sinkretisme: Praktik Ritual Kejawen? - Sulkhan Chakim (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2009)
Javanese people, usually called Kejawen people, believe that all religions teach good values and spiritualpurity to reach perfection in life. They train their spiritual life and inner sense to achieve the highest existence of a human being.When the preaching of Islam came to Java, their rituals and religious practices were influenced by the new values of Islam.Through some dialogical processes, then occurs syncretism as a form of their religious and ritual practices.